أثراللغة العربية في فهم العقيدة الإسلامية: The impact of the Arabic language on understanding the Islamic faith - Sakr, Mohammed Ebrahim; Mohamed El Sayed Mohamed Abdou (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تتعرض الأمة الإسلامية في هذا العصر وفي غيرها من العصور ومنذ أن بزغ نور الإسلام للبشرية ؛ لهجمات عنيفة من قبل أعداء الإسلام ، وهذه الهجمات كثيرة ومتنوعة ؛ فمنها إثارة الشبهات والنيل من الثوابت التي تربت عليها الأمة الإسلامية ، ومحاولة التشكيك في العقيدة الإسلامية ، ومما أثاره الأعداء زعمهم وجود أخطاء لغوية في القرآن الكريم وفي النصوص الشرعية ، وخاصة ما يتعلق بعقيدة التوحيد ، مما جعل البعض يتبع طريق هولاء المشككين ؛ لذا كان الهدف من هذه الدراسة بيان أهمية اللغة العربية في فهم العقيدة الإسلامية الفهم الصحيح ، وشرح بعض النماذج من النصوص الشرعية لتوضيح أهمية اللغة العربية في فهم المراد الصحيح من هذه النصوص ، ولقد سلكت في هذه الدراسة منهج الاستقراء والتحليل ، وذلك بتتبع النصوص التي يحتاج في فهمها إلى فهم قواعد اللغة العربية ، واخترت بعضاً منها للدراسة والتحليل ، وتوصلت إلى عدة نتائج منها : أن اللغة العربية أداة مهمة لايستغني عنها دارس العلوم الشرعية ، وأن سوء الفهم لنصوص القرآن والسنة يرجع إلى إهمال تعلم اللغة العربية والتفقه فيها .وإن سبب ضلال كثير من الناس في الأمور الإعتقادية يرجع إلى ضعف فهم اللغة العربية . ABSTRACT The Islamic nation is exposed in this era and in other eras, and since the light of Islam dawned on humanity; to violent attacks by the enemies of Islam, and these attacks are many and varied; Among them is the raising of suspicions and undermining the constants on which the Islamic nation was brought up, and the attempt to cast doubt on the Islamic faith, and among what the enemies raised was their claim that there were linguistic errors in the Holy Qur’an and in the legal texts, especially with regard to the doctrine of monotheism, which made some follow the path of these skeptics; Therefore, the aim of this study was to demonstrate the importance of the Arabic language in understanding the Islamic faith, the correct understanding, and to explain some examples of legal texts to clarify the importance of the Arabic language in understanding the correct meaning of these texts. Understanding it led to understanding the grammar of the Arabic language, and I chose some of them for study and analysis, and reached several results, including: The Arabic language is an important tool that the student of Sharia sciences cannot do without. Misunderstanding of the texts of the Qur’an and Sunnah is due to neglecting to learn the Arabic language and understanding it. The reason why many people go astray in matters of belief is due to poor understanding of the Arabic language.